Measuring the level of physical activity among students at Tishreen and Hama universities. (Journal of Hama University, 2024)
The research aimed to identify the level of physical activity among students at Tishreen and Hama Universities, as well as to identify differences in the level of physical activity among students at the two universities according to the variables of gender and area of residence (rural – city). The researcher used the descriptive approach to suit the nature of this research on a sample of (380) male and female students from the first year of study, with the exception of students from the Faculty of Physical Education at the two universities. The researcher used the International Physical Activity Questionnaire (IPAQ), short from, as a data collection toll.  The results showed that the level of physical activity among the students is high, There are also statistically significant differences in the level of physical activity depending on the gender variable, In favor of males. The results also showed that there are no statistically significant differences in the level of physical activity according to the variable of area of residence (rural – city). Based on these result, the researcher recommended the necessity of conducting more of this research on other segments of society, as well as providing infrastructure for practicing physical activity and increasing awareness programs about the importance of physical activity and building a national strategy to achieve the aspirations of the World Health Organization regarding physical activity.
Keywords: physical activity – university students.